CONSUMPTION AND UTILIZATION OF CASTOR BEAN LEAVES TREATED WITH NEEM SEED KERNEL EXTRACTS BY THE COTTON LEAF WORM LARVAE, Spodoptera littoralis (Boisd.) - R.M.H Tagour; , H.A. Gomaa; G.M Abd El-Hamed (Arab Universities Journal of Agricultural Sciences, 2010)
Larva of cotton leaf worm, Spodoptera littoralis ate and digested an average of 13.79 and 10.82g, respectively of untreated castor bean leaves during its whole sixth instar. These amounts significantly reduced when larvae were fed on leaves treated with different concentrations of neem seed kernel methanolic extract. The reduction was concentration dependent, i.e., an increase in neem extract concentration caused an obvious decrease in the amount of ingested or digested leaves. The consumption and digestion indices are always negative indicating that treated castor bean leaves are not preferred by S. littoralis larvae for feeding. These indices decreased as the concentrations of neem extract increased. Approximate digestibility in S. littoralis sixth instar larvae averaged 78.50%. This percentage insignificantly fluctuated between 77.71 and 81.08% when larvae were fed on castor bean leaves treated with different concentrations of neem extract. Efficiencies of conversion of ingested and digested food to body substances (ECI and ECD) are an overall indicators for ability of S. littoralis larvae to utilize ingested and digested food for growth and food storage in the insect. Such values depend upon the food digestibility, its nutritional values and the ingestion rates. ECI and ECD in larvae fed on untreated leavesreached 22.25 and 28.25%, respectively. These values decreased after feeding the larvae on treated leaves. The decrease was gradually occurred as the concentration of neem extract increased to reach the minimum value at the highest concentration (0.025%).